Perbedaan Hasil Belajar Ipa Siswa Kelas VII MelaluiPembelajaran Jigsaw Dan Reading Guide Di SMP Negeri 1Kedawung Sragen Semester Genap Tahun Ajaran 2015/2016 - ARDIAN PUTRI, RIKA; Anif, M.Si, Dr. Sofyan Anif, M.Si (2016)
The aims of this research is to know the differences between Jigsaw and Reading Guide learning to the learning outcome of IPA biology for the VII grade students of SMP Negeri 1 Kedawung at even semester in 2015/2016 academic year. This research using true experiment with posttest only control group design method. The population of this research is all of the VII grade students. The sample of this research is three classes which is choosen by purposive sampling. The data which is gotten by observation, documentation, and posttest, while the analyzing of data using one way anova. Before the data is analyzed by the researcher, firstly it is done prerequisite test that are normality and homogenity tests. In the Jigsaw learning gets the average is 75,15 meanwhile in the reading guide gets the average is 81,57 and in the control learning gets the average is 69,57. From the result of data analysis using ANOVA gained the value of Fcount 18,136 > Ftabel 3,10, so H0 refused. The final result showed that there is the differences between Jigsaw dan Reading Guide learning to the learning outcome of IPA biology for the VII grade students of SMP Negeri 1 Kedawung Sragen at even semester in 2015/2016 academic year.